2018
DOI: 10.1007/s00432-018-2729-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy for centrally located hepatocellular carcinoma: outcomes and toxicities

Abstract: In the present cohort, SBRT to the CL-HCC produced excellent treatment response with acceptable HBT and LC. Select HCC patients who are not candidates for surgery or other locoregional therapies can be considered for SBRT to the central liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These findings are consistent with those of the CheckMate 040 trial which demonstrated a 25% rate of grade 3/4 adverse events (no grade 5 events reported) in the dose-escalation arm, primarily due to elevation in laboratory values [10]. Likewise, these data are consistent with previous reports of toxicity among patients undergoing definitive SBRT alone for HCC [13,22].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with those of the CheckMate 040 trial which demonstrated a 25% rate of grade 3/4 adverse events (no grade 5 events reported) in the dose-escalation arm, primarily due to elevation in laboratory values [10]. Likewise, these data are consistent with previous reports of toxicity among patients undergoing definitive SBRT alone for HCC [13,22].…”
Section: Discussionsupporting
confidence: 90%
“…52 Stereotactic ablative body radiotherapy may have an advantage as a non-invasive ablative option for peripheral and subphrenic HCCs as well as the more central tumors abutting biliary structures or major blood vessels. 30,53 Central or left-sided HCCs bordering the duodenum or stomach can present challenges to dose escalation; however, treatment delivery is still feasible with appropriate motion management techniques and dose reductions at the interface. Risk estimates for bowel injury following SABR have been developed with the low-risk limits (< 5% risk of grade ≥ 3 toxicity) generally achievable with the dose ranges used for treating HCC.…”
Section: Patient Selectionmentioning
confidence: 99%
“… 73 It is unclear whether there exists a clear dose response for local control, with differing opinions in the literature. 72 , 86 , 104 Single fraction SBRT (26-40 Gy) led to good local control in phase I/II trials for liver metastases, while reports on its application in HCC are limited. [105] , [106] , [107] The critical luminal structures and healthy non-tumorous liver often limit the dose delivered.…”
Section: Future Directionsmentioning
confidence: 99%